THE EFFECTIVENESS OF LITERACY TEACHING MATERIALS BASED ON LOCAL WISDOM IN IMPROVING LITERACY SKILLS FOR ELEMENTARY SCHOOL STUDENTS - Ifah Hanifah; Muchlas Suseno; Miftahulkhairah Anwar (JALL (Journal of Applied Linguistics and Literacy), 2022)
Teaching materials are a factor that can determine success in achieving a particular skill. Therefore, in improving students' literacy skills, teaching materials are needed as support. So, a study was conducted under the title "The Effectiveness of Local Wisdom-Based Literacy Teaching Materials for Elementary School Students" "This study aims to examine local wisdom-based literacy teaching materials for elementary school students. The objective is based on the formulation of the problem "how is the effectiveness of local wisdom-based literacy teaching materials for elementary school students?. This study uses a quasi-experimental method using a pre-experimental design with one control group pretest-posttest design. The object of this research is elementary school students in grade 5 at SDN 1 Ciloa Kuningan Regency using a research instrument as a test. The experiment was carried out for three days by conducting a pretest, treatment, and post-test. Based on the results of data analysis, it was found that literacy teaching materials based on local wisdom effectively improved the literacy skills of 5th graders at SDN 1 Ciloa. This is evident from the differences in students' literacy skills before and after being given literacy teaching materials based on local wisdom. In the Paired Samples Statistics table, the score of sig. (2-tailed) is 0.001 < 0.05, then H0 is rejected, and Ha is accepted. So that it can be concluded that there is an average difference between the pretest and post-test learning outcomes.